Automotive Service : Inspection, maintenance, repair - Gilles, Tim (Cengage Learning, 2016)
Book helps you develop the knowledge and skills you need for career success. Known for its clear explanations and high quality art, the book includes step-by-step procedures for trouble-shooting and repair.